2021
DOI: 10.3389/fmed.2021.690100
|View full text |Cite
|
Sign up to set email alerts
|

Altered Distribution of Circulating T Follicular Helper-Like Cell Subsets in Rheumatoid Arthritis Patients

Abstract: Objective: Recent studies on follicular regulatory T (Tfr) and follicular helper T (Tfh) cells suggest that they may participate in the pathogenesis of rheumatoid arthritis (RA). Here, we examine Tfr-like and Tfh-like cells and their subsets in RA and assess the correlations between these subsets with B cells and cytokines related to the pathogenesis of RA and their clinical significance.Methods: The study population consisted of 18 healthy controls and 47 RA patients (17 new onset, 57.00 ± 11.73 years; 30 tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
1
8
1
Order By: Relevance
“…In agreement with a wealth of data showing an expansion of circulating Tfh cells in RA patients ( 19 , 20 , 22 , 29 , 38 46 ), we report here an increased frequency of tTfh cells, defined as CD25 lo CD127 hi CXCR5 + CD45RA neg CD4 + CD3 + cells, in blood from RA patients, particularly those that present autoantibodies and are untreated. In addition, we detected a high frequency of CCR7 lo PD1 hi and IL-17 + IFNγ neg Tfh cell subsets in seropositive RA patients.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with a wealth of data showing an expansion of circulating Tfh cells in RA patients ( 19 , 20 , 22 , 29 , 38 46 ), we report here an increased frequency of tTfh cells, defined as CD25 lo CD127 hi CXCR5 + CD45RA neg CD4 + CD3 + cells, in blood from RA patients, particularly those that present autoantibodies and are untreated. In addition, we detected a high frequency of CCR7 lo PD1 hi and IL-17 + IFNγ neg Tfh cell subsets in seropositive RA patients.…”
Section: Discussionsupporting
confidence: 92%
“…Data from human studies on cTfh cells in RA patients clearly corroborate mouse data on aberrant Tfh numbers (Table 1). Several studies have reported an increase in cTfh cells in RA patients, accompanied by elevated IL-21 levels in some cases [65][66][67][68][69][70][71]. However, it is important to note that while there are increase Tfh numbers both in murine and human GCs, the underlying mechanism responsible for their expansion remains to be fully unraveled.…”
Section: Defective Tfh Cell Functioning Within Gcsmentioning
confidence: 97%
“…Arroyo-Villa et al [65] RA patients with active disease have a higher frequency of Tfh cells and a higher Tfh/Tfr ratio resulting from lower Tfr frequencies Zhang et al [66] Increased frequencies of Tfh cells and IL-21 in RA patients which correlates positively with DAS28 Wang et al [67], Zhou et al [69] Increased frequencies of Tfh cells in newly diagnosed RA patients correlating with activated B cells and DAS28 Niu et al [68] Elevated frequencies of Tfh cells, IL-21 and PD-1 in RA patients with active disease Nakayamada et al [70] Higher proportions of Tfh cells in RA patients with active disease and, treatment with Abatacept reduces Tfh cell levels. Su et al [71] Elevated frequencies of Tfh cells in RA patients compared to HCs…”
Section: Tfh Cells In Ra Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies into the role of T cells in the pathogenesis of RA in humans have mainly focused on the well-known Th1, Th2, Th17, and Treg subsets [ 21 , 22 , 23 ], during established disease, and in cell populations from peripheral blood and inflamed joints [ 22 , 24 ]. Studies of Tfh cells have focused on peripheral blood samples or inflamed tissue [ 4 , 25 , 26 , 27 ], while studies investigating Tfh cells in lymphoid organs during the earliest phases of autoimmunity are lacking. To the best of our knowledge, no study has analyzed CD8 + Tfh during the various stages of RA.…”
Section: Introductionmentioning
confidence: 99%